Shaping Teachers' Character and Workplace Well-Being: A Multi-Site Study on Principal Leadership for SDG 4 and SDG 8 - Al Hadi; Dewie Tri Wijayanti Wardoyo; Amrozi Khamidi (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To analyze principal management in shaping teacher character through planning, organizing, implementation, and supervision at SMP Negeri 1 Sidoarjo and SMP Negeri 3 Krian, Sidoarjo. Method: Employing a qualitative approach using a multi-site case study design. Data were collected through observation, in-depth interviews with principals, teachers, and students, as well as document analysis. The data were analyzed using cross-case analysis to identify similarities, differences, and management patterns applied by principals in shaping teacher character. Results: The findings show that the principal of SMP Negeri 1 Sidoarjo applied systematic, structured, and data-based management to strengthen accountability in planning, organizing, implementation, and supervision. In contrast, the principal of SMP Negeri 3 Krian emphasized flexible, contextual, collaborative, and humanistic management through intensive interpersonal communication and a family-oriented school culture. These different approaches indicate that teacher character development can be strengthened through both formal data-based management and humanistic interpersonal leadership. Novelty: Proposing a conceptual model of principal management in shaping teacher character consisting of five key components: leadership through real exemplary behavior, integration of data-based management and humanistic approaches, strengthening of distinctive school culture, improvement of teacher professionalism and performance, and optimization of effective organizational performance. This model offers a practical and theoretical framework for schools seeking to improve teacher character, school culture, graduate quality, student character formation, and public trust in educational institutions for SDG 4 and SDG 8.